Government and Private Sector Collaboration in Handling the Covid-19 Pandemic in Indonesia - Sjamsoeddin, Sjafrie; Yoesgiantoro, Purnomo; Saragih, Herlina Juni Risma; Soepandji, Budi Susilo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The COVID-19 pandemic in 2021 still has not shown a significant decline. Even the President of the Republic of Indonesia stated that COVID-19 is factually still occurring by issuing Presidential Decree No. 24 of 2021 concerning Determination of the Factual Status of the Corona Virus Disease 2019 (COVID-19) Pandemic in Indonesia. Policy measures and cooperation are needed to face the ongoing pandemic's challenges, especially in the economic, social, and resource fields. This also means that collaboration between the government and the private sector is essential in handling the COVID-19 pandemic in Indonesia. In this collaboration, there are supporting factors and inhibiting factors. Supporting factors include shared motivation, leadership, and institutional procedures or provisions. Meanwhile, the inhibiting factors include policies issued by the government and the private sector, whose business and economic factors are predominantly affected by COVID-19. Government and private sector collaboration in handling COVID-19 can be carried out with several approaches: health security capacity, availability of health services, response management, PentaHelix and vaccination, promotive and preventive efforts, response actions, detective actions, and preventive actions.